MOTIVASI BERPRESTASI MAHASISWI KEPELATIHAN JURUSAN PENDIDIKAN OLAHRAGA FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS RIAU - Fadillah Sari Ananda; Hesti Asriwandari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research was conducted at the Campus Physical Education who is in Rumbai. The purpose of this study was to determine student achievement motivation in selecting a course of coaching. This study entitled